Managing Rangeland as a Complex System: How Government Interventions Decouple Social Systems from Ecological Systems - Wenjun Li; Yanbo Li (Ecology and Society, 2012)
The complexity of natural resource management is increasingly recognized and requires adaptive governance at multiple levels. It is particularly significant to explore the impacts of government interventions on the management practices of local communities and on target social-ecological systems. The Inner Mongolian rangeland was traditionally managed by indigenous people using their own institutions that were adapted to the highly variable local climate and were able to maintain the resilience of the social-ecological system for more than 1000 years. However, external interventions have significantly affected the rangeland social-ecological system in recent decades. In this paper, using livestock breed improvement as an example, we track government interventions from the traditional era through the collective period to the present market economy period based on a review of historical documents and case studies. Using the concept of social-ecological system resilience, we diagnose the impacts of interventions on livestock breed management in the rangeland social-ecological system, and discuss how these interventions occur. We found that government interventions in livestock breeding have gradually decoupled the pastoral society from its supporting ecological system. During this process, external powers have increasingly displaced the local community in defining the nature of rangeland management. Power asymmetry and discourse have contributed to this displacement.